Outcome of simultaneous bi-unicompartmental knee arthroplasty: a systematic review - Akkawi, Ibrahim; Draghetti, Maurizio; Zmerly, Hassan (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Simultaneous medial and lateral tibiofemoral osteoarthritis (OA) could be treated with bi-unicompartmental knee arthroplasty (Bi-UKA) as an alternative to total knee arthroplasty (TKA). The present systematic review aims to assess if simultaneous Bi-UKA is a feasible option for treating medial and lateral tibiofemoral OA. Materials and Methods: A comprehensive search of PubMed, MEDLINE, Cochrane Library, and Google Scholar was performed to find studies that reported on the outcome of simultaneous Bi-UKA for both medial and lateral tibiofemoral OA. Results: Seven studies were considered eligible for inclusion in the present systematic review. Intraoperative fractures occurred 8 times. Overall, there were 22 revisions of the prosthetic components for any reason with a survival rate that ranged from 83 to 100%. Of these, 16 revisions were for the aseptic loosening of the prosthetic components. Out of 302 surgeries, three were revised due to symptomatic OA progression in the patello-femoral joint. All clinical scores improved at the latest follow-up compared to preoperative values. Moreover, there were no differences in clinical scores of Bi-UKA compared to unicompartmental knee arthroplasty (UKA), or medial UKA plus patello-femoral prosthesis. Whereas, compared to TKA, Bi-UKA patients had comparable or superior scores. Finally, the Bi-UKA group had a significantly shorter hospital stay compared to the TKA group. Conclusions: The use of simultaneous Bi-UKA is a valid option to address bicompartmental knee OA in selected patients with low intraoperative fracture rate, low revision rate, satisfactory clinical outcome, and fast recovery.